SPATIAL MODELING OF RISK FACTORS FOR UNDER-FIVE PNEUMONIA IN ROKAN HILIR DISTRICT, INDONESIA - YUSDIANA, Yusdiana; SUKENDI , Sukendi; SIREGAR , Yusni Ikhwan; AFANDI , Dedi (African Journal of Infectious Diseases (AJID), 2025)
Background: Under-five pneumonia poses a critical health issue that significantly affects children in Indonesia. Identifying risk factors based on spatial models is essential for developing comprehensive and sustainable disease-prevention strategies. Objectives: This study aimed to identify risk factors and develop a spatial model of the distribution of under-five pneumonia cases in Indonesia based on regional vulnerability. Materials and Methods: This study used a mixed-method approach that integrated mathematical models and GIS to identify risk factors using the GPR model and developed a GIS-based spatial model with IDW and natural break methods. Results: The GPR model found that an increase in under-five pneumonia cases was associated with population density (β = 0.004, Z-score = 6.118), rainfall (β = 0.002, Z-score = 6.031), malnutrition (β = 1.786, Z-score = 3.696), and health facilities (β = 0.073, Z-score = 13.527). In contrast, exclusive breastfeeding (β = -0.004, Z-score = -2.874), healthy homes (β = -0.021, Z-score = -9.532), and under-five health service coverage (β = -0.003, Z-score = -2.225) decreased under-five pneumonia cases. The spatial distribution model of vulnerable regions by risk factors resulted in the classification of high-risk (5 subdistricts), medium-risk (11 subdistricts), and low-risk (3 subdistricts) areas. Conclusion: This study confirmed significant risk factors and the spatial distribution of vulnerability levels for under-five pneumonia. The results highlight the need for comprehensive and integrated program interventions targeting vulnerable areas to achieve the global goal of reducing the incidence of pneumonia to less than 12 cases per 1,000 children under five in 2030.